1985
DOI: 10.1111/j.1651-2227.1985.tb10921.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Postnatal Weight Loss and Subsequent Weight Gain in Small for Dates Newborn Infants

Abstract: ABSTRACT. Using a sucrose and deuterium oxide dilution technique body water compartments and solids were serially determined in small for dates newborn infants at birth, at the moment of maximum postnatal weight loss and on recovery of birth weight. Compositions of weight loss and subsequent weight gain were calculated from the differences in body water compartments and solids between the first and the second and the second and the third study, respectively. Birth weight of the infants was 1.55 ± 0.46 kg (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 12 publications
3
13
0
2
Order By: Relevance
“…[7][8][9] This observation is consistent with the notion that in intrauterine growth restricted or SGA infants, the higher body water content is due to a lower lean body mass and fat content when expressed as percent birth weight. 10 Thus, it is somewhat counterintuitive to have a lower incidence of EPWL in SGA infants since the expectation is that a larger body fluid content 3,4 would result in more fluid loss after birth with greater accompanying weight loss.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…[7][8][9] This observation is consistent with the notion that in intrauterine growth restricted or SGA infants, the higher body water content is due to a lower lean body mass and fat content when expressed as percent birth weight. 10 Thus, it is somewhat counterintuitive to have a lower incidence of EPWL in SGA infants since the expectation is that a larger body fluid content 3,4 would result in more fluid loss after birth with greater accompanying weight loss.…”
supporting
confidence: 79%
“…Previous studies [7][8][9] have shown that small for gestational age (SGA) infants have a different body composition when compared with appropriate for gestational age (AGA) infants. Because SGA infants have less lean body mass and fat when expressed per kilogram body weight, their body water content is higher than their AGA counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBW was determined from the distribution volume of DjO using an infrared spectrophotometric method [8]. Both methods have recently been described by us in more detail [10]. Intracellular water volume (ICW) was calculated as TBW-ECW.…”
Section: Measurement O F the Body Water Compartmentmentioning
confidence: 99%
“…Sucrose has been used in adults as an indicator of extracellular volume (3)(4)(5)(6). The first pediatric study using sucrose was done in small-for-gestationalage preterm infants (7). The authors assumed a mono-exponential concentration-time curve, but did not investigate sucrose pharmacokinetics in this particular patient population.…”
mentioning
confidence: 99%